CONSUMER BEHAVIOR TOWARDS MANGROVE ECOTOURISM IN MEMPAWAH REGENCY - Wahyuni, Wahyuni; Dolorosa, Eva; Imelda, Imelda (Jurnal Sains Pertanian Equator, 2019)
Mempawah Mangrove Park has a great potential in ecotourism. It has some qualities such as the strategic location, has a good and neat condition, and adequate facilities. The purpose of this research is to know the consumer behavior toward Mempawah Mangrove Park ecotourism in the Mempawah districts. It takes place in Mempawah Mangrove Park, Pasir village, Mempawah Hilir sub-district, Mempawah Regency. Responden of this study were ecotourism visitors of mangrove Park with the number of respondents is 100. This research used Fishbein analysis. The result showed that the behavior of consumer was good as the score of 16,6086 which means the visitors have positive contribution on Mempawah Mangrove Park. Cosumer behavior can be improved on toilet cleanliness by increasing the control of ecotourism officers. Key Words : Consumer behavior, Ecotourism, Fishbein, Mangrove